Profesionalisme Guru Ditinjau Dari Pengalaman Mengikuti Kegiatan Ilmiah Dan Implementasi Kurikulum 2013 Pada Sekolah Menengah Atas Negeri Kecamatan Banjarsari Tahun 2015/2016 - Maharani, Rida Kusuma; , Dra. Titik Asmawati, SE, M.Si (2016)
Rida Kusuma Maharani. A210120104. Economic Accounting Study Program. The Faculty of Education, University of Muhammadiyah Surakarta, 2016. The purpose of this research are: 1) To determine the effect of teacher experience following the scientific activities in the professionalism of teachers. 2) To determine the effect of the application of curriculum implementation in 2013 in the professionalism of teachers. 3) To determine the effect of teacher experience to follow the scientific activities and curriculum implementation in 2013 in the professionalism of teachers. This research is associative quantitative research with a conclusion through statistical methods. The population in this study amounted to 161 are all teachers of SMA District of Banjarsari in SMA Negeri 1 Surakarta and SMA Negeri 2 Surakarta. samples are taken as 110 teachers with Proportional Random Sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 9,140 + 0,396 X1 + 0,457 X2. The equation shows that the professionalism of teachers affected by the experience of teachers follow the scientific activities and implementation of curriculum implementation, 2013. The conclusions drawn are: 1) Experience teachers follows the scientific activities in the professionalism of teachers acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 7.668> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 40% and the effective contribution of 23.3%. 2) Implementation of curriculum implementation in 2013 in the professionalism of teachers acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 9.412> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 60% and 35% effective contribution. 3) Experience teachers follows the scientific activities and implementation of curriculum implementation in 2013 in the professionalism of teachers acceptable. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 74.656> 3.150 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.583 indicates that the influence of teacher experience following the scientific activities and implementation of curriculum implementation in the professionalism of teachers in 2013 amounted to 58.3%, while the rest influenced by other variables.